‘Would You Prefer Jail or Probation?’ Differences in Sanctioning Preferences among White, Black, and Latinx Adults - Wodahl, Eric J. (The prison journal, 2022)
Research on perceptions of sanction severity reveals a gap between White and Black respondents in terms of their preferences for incarceration compared to alternative punishments. Little is known, however, about Latinx preferences. Using a sample of jail inmates, we explore differences across White, Black, and Latinx respondents in terms of their preferences for incarceration versus probation, as well as the factors that relate to these preferences. Findings show that White respondents prefer probation far more frequently than Black and Latinx respondents. Additionally, factors which relate to sanctioning preferences for Whites are fundamentally different than those for Black and Latinx adults.